Territórios da agroindústria de laticínios em Nossa Senhora da Glória - SE - Andrade Junior, Janison Correia de (2018)
Territories can arise from the most varied manners that man has to relate to space, and from this he can take multiple forms. For this to happen, a series of actions brought about by the action of individuals acting under the physical substrate must be concretely manifested, provoking diverse consequences within a specific reality. In the Brazilian municipality of Nossa Senhora da Glória, in the State of Sergipe, the dairy agroindustry appears to operate within a traditional market in the area, that one of the milk. Its activities, being then a direct result of human action, generate environmental and cultural impacts that are taken into account in the configuration of several territories. Therefore, this study has as general objective to analyze the environmental and cultural impacts of dairy agroindustry in the configuration of its territories. For that, bibliographical surveys were made to discuss these concepts as a category of geographic science study; of Environmental Impacts seeking to overcome its simplistic approach and Cultural Impacts from a perspective of the discussions that involve the concept of culture. Access to previous research involving or addressing the object of study provided rich information as well as economic, historical and social analyzes involving the area of the object studied. Allied to these premises, the observation in the field of social realities in the area of study and in its adjacent context served to confront the theoretical knowledge. From all these prerogatives, it was possible to verify the presence of multiple territories that arise from the agroindustrial activities of dairy in its environmental and cultural impacts.